PENGARUH PEMAHAMAN, KUALITAS PELAYANAN DAN KETEGASAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Pada Pengusaha UKM di Daerah Kota Semarang) (Students' Journal of Accounting and Banking, 2013)
The purpose of this study was to determine the influence of comprehension, service quality and assertiveness sanctions towards tax compliance, to tax compliance.The object of research are SMEs Enterpeneur in the Region of Semarang. The data used is primary data. Sample used in this study amounted to 86 respondents with a convinience sampling technique. The analisis data use multiple regression model.The results showed that the test variable comprehension, service quality and firmness of sanctions affect the taxation has a positive and significant influence of tax compliance. Compehension has dominant affect to tax compliance.Keywords: Small and Medium Enterprises, Tax Comprehension, Quality of services, Assertiveness Sanctions, Tax Compliance